Inverse kinetic isotope effects in the charge transfer reactions of ammonia with rare gas ions. Issue 29 (1st July 2021) - Tsikritea, A.; Park, K.; Bertier, P.; Loreau, J.; Softley, T. P.; Heazlewood, B. R.
Abstract : Inverse kinetic isotope effects are observed in the charge transfer reactions of rare gas ions with ammonia molecules. Abstract : In the absence of experimental data, models of complex chemical environments rely on predicted reaction properties. Astrochemistry models, for example, typically adopt variants of capture theory to estimate the reactivity of ionic species present in interstellar environments. In this work, we examine astrochemically-relevant charge transfer reactions between two isotopologues of ammonia, NH3 and ND3, and two rare gas ions, Kr + and Ar + . An inverse kinetic isotope effect is observed; ND3 reacts faster than NH3 . Combining these results with findings from an earlier study on Xe + (Petralia et al., Nat. Commun., 2020, 11, 1), we note that the magnitude of the kinetic isotope effect shows a dependence on the identity of the rare gas ion. Capture theory models consistently overestimate the reaction rate coefficients and cannot account for the observed inverse kinetic isotope effects. In all three cases, the reactant and product potential energy surfaces, constructed from high-level ab initio calculations, do not exhibit any energetically-accessible crossing points. Aided by a one-dimensional quantum-mechanical model, we propose a possible explanation for the presence of inverse kinetic isotope effects in these charge transfer reaction systems.